Pengaruh Akuntabilitas Pengelolaan Keuangan Alokasi Dana Desa, Kebijakan Desa Dan Kelembagaan Desa Terhadap Kesejahteraan Masyarakat Pada Nagari Sungai Tanang Kecamatan Banuhampu Kabupaten Agam - Lasmi Yupita; Verni Juita (Universitas Batanghari Jambi, 2020)
This research was conducted on the community in Nagari Sungai Tanang District of Banuhampu Agam Regency. The purpose of this study was to examine the effect of accountability on financial management of village fund allocations, village policies and village institutions on community welfare. This type of research is quantitative penenlitian. The object of this research is Nagari Sungai Tanang. Sampling method used is stratified random sampling and data is processed by multiple linear regression analysis, validity test, realibility and hypothesis testing with F test and t test. The result of the research with the t-test of accountability management of Village Fund Allocation (ADD) is 0,034 <0,05 so it shows that accountability of Village Fund Allocation (ADD) influence posistif to welfare of society, while tsign of village policy equal to 0,000 <0,05 so indicate that policy villages have a positive effect on the welfare of the community, and the institutional tsign of the village with the amount of 0.001 <0.05 indicating that the village institutions have a positive effect on the welfare of the community.